International Journal of Literature and Language Studies Vol.4 No.5 - Vol.4 No.6 (International Journal of Literature and Language Studies, 2025)
International Journal of Literature and Language Studies is an international online academic journal dedicated to publishing high-quality scholarly research in the fields of literature, linguistics, language education, cultural studies, and interdisciplinary humanities research. The journal provides an academic platform for researchers, lecturers, students, and independent scholars from around the world to share innovative ideas, theoretical perspectives, and original research findings.